2015
DOI: 10.1038/ncb3206
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal inhibition of Atg7 prevents tumour initiation through a microbiome-influenced immune response and suppresses tumour growth

Abstract: Here, we show that autophagy is activated in the intestinal epithelium in murine and human colorectal cancer and that the conditional inactivation of Atg7 in intestinal epithelial cells inhibits the formation of pre-cancerous lesions in Apc(+/-) mice by enhancing anti-tumour responses. The antibody-mediated depletion of CD8(+) T cells showed that these cells are essential for the anti-tumoral responses mediated by the inhibition of autophagy. We show that Atg7 deficiency leads to intestinal dysbiosis and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 62 publications
10
150
1
4
Order By: Relevance
“…2B and D). A growing body of evidence indicates that similar elimination of signaling molecules play key roles in autophagy-regulated immune responses (53)(54)(55)(56)(57). For instance, microglial autophagy plays an important role in the clearance of extracellular Aβ (β-amyloid) fibrils and the regulation of Aβ-induced inflammation, thereby affecting neuronal viability (53).…”
Section: Discussionmentioning
confidence: 99%
“…2B and D). A growing body of evidence indicates that similar elimination of signaling molecules play key roles in autophagy-regulated immune responses (53)(54)(55)(56)(57). For instance, microglial autophagy plays an important role in the clearance of extracellular Aβ (β-amyloid) fibrils and the regulation of Aβ-induced inflammation, thereby affecting neuronal viability (53).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular antigen presentation via MHC class I molecules is also regulated by the autophagy machinery, because autophagy‐related proteins enhance MHC class I internalization for degradation and thereby diminish antigen display on the cell surface 268. Indeed, in vivo studies have primarily found enhanced CD8 + T cell responses in mice with defective autophagy in antigen‐presenting cells268, 269, 270 A potential mechanism leading to such increased CD8 + T cell expansions is that, in the absence of autophagy, more substrate becomes available for canonical MHC class I loading271 or by decreased endocytosis and degradation of cell surface MHC class I molecules 268. Thus, defective autophagy in skeletal muscle fibers could drive increased MHC class I expression and CD8 + T cell accumulation.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%
“…It has been suggested to hold a tumour suppressive function during early tumourigenesis, [20][21][22][23][24][25][26][27] whereas it can also sustain cancer progression. [28][29][30][31][32][33][34][35][36] Increased levels of basal autophagy have been found in a variety of cancer tissues including colorectal cancer (CRC), where autophagy supports tumour growth and confers tumour aggressiveness. 31 Autophagy is inhibited by oncogenic tyrosine kinases (OncTKs) and receptor tyrosine kinases (RTKs) via activation of the PI3K/AKT/mTORC1 and RAS/MAPK signalling.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36] Increased levels of basal autophagy have been found in a variety of cancer tissues including colorectal cancer (CRC), where autophagy supports tumour growth and confers tumour aggressiveness. 31 Autophagy is inhibited by oncogenic tyrosine kinases (OncTKs) and receptor tyrosine kinases (RTKs) via activation of the PI3K/AKT/mTORC1 and RAS/MAPK signalling. 37 In this respect, work from our group and others has shown that induction of autophagy upon pharmacological targeting of OncTKs/RTKs promotes survival.…”
Section: Introductionmentioning
confidence: 99%